Perceptions and experiences related to health and health inequality among rural communities in Jimma Zone, Ethiopia: a rapid qualitative assessment - Nicole Bergen; Abebe Mamo; Shifera Asfaw; Lakew Abebe; Jaameeta Kurji; Getachew Kiros; Muluemebet Abera; Gebeyehu Bulcha Duguma; Kunuz Haji Bedru; Manisha A. Kulkarni; Ronald Labonté; Sudhakar Morankar (BMC, 2018)
Abstract Background The Safe Motherhood Research Project studies the implementation and scale-up of maternal, newborn and child health (MNCH) initiatives in Jimma Zone, Ethiopia. This qualitative rapid assessment study was undertaken to explore community perceptions and experiences related to health, health inequality and other MNCH themes. Methods We conducted 12 focus group discussions and 24 in-depth interviews with community stakeholder groups (female and male community members, Health Extension Workers, members of the Women Development Army and Male Development Army, and religious leaders) across six rural sites in Jimma Zone. Data were analyzed through thematic coding and the preparation of content summaries by theme. Results Participants described being healthy as being disease free, being able to perform daily activities and being able to pursue broad aspirations. Health inequalities were viewed as community issues, primarily emanating from a lack of knowledge or social exclusion. Poverty was raised as a possible contributor to poor health, however, participants felt this could be overcome through community-level responses. Participants described formal and informal mechanisms for supporting the disadvantaged, which served as a type of safety net, providing information as well as emotional, financial and social support. Conclusions Understanding community perceptions of health and health inequality can serve as an evidence base for community-level initiatives, including MNCH promotion. The findings of this study enable the development of audience-centered MNCH promotion activities that closely align with community priorities and experiences. This research demonstrates the application of rapid qualitative assessment methods to explore the context for MNCH promotion activities.